Inovasi Biskuit Pakan Inovasi Biskuit Pakan Kulit Ubi Jalar (Ipomoea Batatas L.) sebagai Alternatif Pakan Feedlot Domba Wonosobo - Ana, Angelli; Hidayatullah, Abdul Rouuf; Arumsari, Cahyaning Asri; Puspitaningrum, Venika (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
BPS data in 2021, since 2018 the sheep population has increased, but in 2022 the sheep population decreased by 0.13% compared to the previous year. The use of sweet potato skin waste can be used as a feed innovation that can support the growth performance of sheep without incurring excessive costs. This study aims to utilize sweet potato skin waste as feed for Wonosobo sheep, so that environmental problems can be resolved by having a high selling value. Livestock absorb energy in feed, especially for basic living needs. The use of 30% sweet potato skin as the basic ingredient can produce energy of 888Kcal/kg with a PK (Crude Protein) content of 0.48%, the use of concentrate as much as 28% of the energy that can be produced is 812Kcal/kg and a PK content of 6.16%, butterfly pea leaves are the third ingredient with use in rations as much as 21% with a total energy produced of 3,969Kcal/kg and a PK content of 4.62%.